Implications of non-invasive prenatal testing for identifying and managing high-risk pregnancies. (January 2021) - Merriel, Abi; Alberry, Medhat; Abdel-Fattah, Sherif
Abstract: Non-invasive prenatal testing is regularly used to screen for aneuploidies and Rhesus status of a fetus. Since 1997 when free fetal DNA (ffDNA) in the maternal circulation was first identified, it has been hypothesized that it may be possible to use non-invasive prenatal testing (NIPT) to identify high-risk pregnancies including pre-eclampsia, growth restriction and preterm birth. Since then there has been much interest in this area as a way to identify and understand disease processes. This review presents the current evidence for this approach. For pre-eclampsia the hypothesis is that ffDNA would increase but the evidence for this is heterogenous across studies and trimesters. There is however increasing agreement between studies that by the third trimester ffDNA is more likely to be raised in pre-eclamptic patients than controls. For preterm birth, again, the main hypothesis is that ffDNA should increase. The results are also heterogenous, with some studies finding increased ffDNA prior to preterm birth, and others finding no change. For fetal growth restriction, there are competing theories for reduced and increased ffDNA and some studies suggest that levels are raised and some reduced. There are complexities in interpreting all of this evidence as the studies' designs, patient populations, and especially in the context of growth restriction, the definitions are not clear. Furthermore, authors use different biochemical tests and different units to describe their results, making meta-analysis difficult. All of these issues and conflicting findings lead us to the conclusion that currently there is yet no definitive place in clinical practice for NIPT to support the diagnosis and management of high-risk pregnancies. However, it is vital that this research continues as it could open the door to better understanding of the disease process and novel approaches to management.